Effects of marine growth and hydrodynamic loading on offshore structures - Jusoh, Iberahin (Faculty of Mechanical Engineering, UTM, 1996)
Marine growth is known to give adverse effects on the performance of offshore structure. It presents will roughened the surfaces of the structure hence increase its drag coefficients. Structures with the best protection scheme from marine organisms would after few years start to be covered by various types of growth. Generally, it was also recognised that the most important source of loading exerted on offshore structure comes from hydrodynamic action which are influenced by CD and CA,f values. In this paper type of marine growth usually found on offshore structures are mentioned and their effects on hydrodynamic loading are highlighted. Usual ways of controlling and removals of marine growth are also discussed Data of marine growth distribution on a typical structure are presented and discussed.